The relevance of livestock MRV in East and Southern Africa - Dijk, Suzanne van; Wassie, Shimels Eshete; Wilkes, Andreas (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The livestock sector is a key contributor to countries’ greenhouse gas emissions in East and Southern Africa. The relevance of the livestock sector is acknowledged in countries’ NDCs, where the sector is prioritized for climate change mitigation and adaptation. To access climate finance and enable climate change mitigation efforts in the livestock sector, knowledge of (practical) methods for monitoring, reporting, and verification (MRV) of greenhouse gas emissions is essential. Advanced IPCC Tier 2 methods are required to establish detailed livestock emission profiles, identify the emission reduction potential and help policymakers prioritize livestock interventions.